Dissection of Incomplete Fissure Using Electrocautery Is a Safe and Acceptable Method for Thoracoscopic Right Upper Lobectomy - Xu, Hao; Zhang, Linyou (The Thoracic and Cardiovascular Surgeon, 2019)
Objective The incidence of prolonged air leak may be highest after right upper lobectomy due to incomplete minor fissure. The objective of this study was to compare the efficacy of direct electrocautery division and suture with that of a fissureless technique during thoracoscopic right upper lobectomy with incomplete fissure.Methods One hundred and two patients underwent right upper lobectomy between January 2016 and December 2016. Of these, 60 patients underwent a right upper lobectomy conducted using the fissureless technique (group A), and 42 consecutive patients underwent a right upper lobectomy via electrocautery division of the fissure and suture (group B). The preoperative, operative, and postoperative parameters were compared between the two groups.Results The electrocautery and suture group had a higher incidence of prolonged air leak (> 5 days) (30% [12/40] vs 11% [7/62], p = 0.00), a higher incidence of air leakage (20 [32%] vs 38 [95%], p = 0.00), a longer air leak duration (days) (4.93 ± 0.86 vs 3.00 ± 1.60 days, p = 0.00), a longer duration of chest tube (mean 5.30 ± 1.20 vs 3.13 ± 1.88 days, p = 0.00), and a lower hospitalization cost (6463.28 ± 958.30 vs 7459.07 ± 1185.00 €, p = 0.00) than did the fissureless technique group. No differences were observed with respect to patient characteristics, operative characteristics, perioperative mortality, or duration of hospital stay after surgery.Conclusions The number of patients with prolonged air leak was higher in the electrocautery group. However, electrocautery does not prolong overall length of stay and decreases hospitalization costs. Dissection of incomplete fissure using electrocautery is a safe and acceptable method for thoracoscopic right upper lobectomy.
Keywords: thoracoscopy/VATS; surgery; complications; lung cancer treatment; lobectomy